In Silico Assessment of GSK-3? Inhibition Activity by Secondary Metabolites of Centella asiatica in the Development of Alzheimer’s Therapy - Azariani, Wiwin; Ananto, Agus Dwi; Maulidya, Selvira Anandia Intan (Journal of Tropical Pharmacy and Chemistry, 2025)
Alzheimer’s disease involves excessive activity of glycogen synthase kinase-3? (GSK-3?), leading to tau hyperphosphorylation and neurofibrillary tangle formation. This study evaluated the potential of secondary metabolites from Centella asiatica as GSK-3? inhibitors using in silico molecular docking. The GSK-3? structure (PDB ID: 1Q5K) and ten test compounds were docked using YASARA-structure, with method validation yielding an RMSD of 1.890 Å. Naringin, luteolin, and betulinic acid demonstrated the strongest binding affinities -9.2670, -8.1520, and -7.9730 kcal/mol, surpassing the native ligand. Naringin and luteolin interacted with key ATP-binding residues (Asp133, Tyr134, Val135, Lys85), indicating strong competitive inhibitory potential. These findings suggest that C. asiatica metabolites, particularly naringin and luteolin, are promising natural candidates for GSK-3? inhibitor Alzheimer’s therapy.   Keywords:          Centella asiatica; GSK-3?; Molecular Docking; Alzheimer’s Disease; Secondary Metabolites